Goals and Objectives of Physical Education of School Children - Shomuratov Askar Abdullaevich (International Journal on Orange Technologies, 2021)
In accordance with the decision of the President and the Cabinet of Ministers of the Republic of Uzbekistan on measures for further development of physical culture and sports in the Republic of Uzbekistan, special tests "Alpomish" and Barchinoy were introduced in 2000. Alpomish and Barchinoy special tests are the program and normative basis of the system of physical education of the population of Uzbekistan.